Impeachment: towards the juridization of “constitutional offense law” and the identification of “constitutional types” - Sar Suárez, Omar (2024)
The purpose of this article is to analyze the figure of impeachment regulated in the Constitution of Peru of 1993 and developed by the subsequent jurisprudence of the Constitutional Court. We maintain that the Constitution has provided for offending conducts and in that order we identify, specifically, the types of constitutional offense that can give rise to a sanction, which we call the “constitutional types”. For this reason, we state that the trial is political due to the nature of the organ that carries it out, but not because it can be resolved with merely political criteria, rather than on the contrary, the demands of the democratic State impose respect for principles such as legality or due process. The violation of the constitution can only be sanctioned when a senior State official acts against what is constitutionally prohibited or fails to act in alignment with what is constitutionally ordered since constitutional provisions cannot be interpreted as merely programmatic norms or simple recommendations. We conclude that it is essential to juridize constitutional offense law, the core of which is built around the identified “constitutional types” along with the responsibility of senior State officials for what the Ombudsman’s Office calls “unconstitutional misconduct”.